The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.7717/peerj.4960
|View full text |Cite
|
Sign up to set email alerts
|

Biological nitrification inhibition by root exudates of native species,Hibiscus splendensandSolanum echinatum

Abstract: Australian native species grow competitively in nutrient limited environments, particularly in nitrogen (N) limited soils; however, the mechanism that enables this is poorly understood. Biological nitrification inhibition (BNI), which is the release of root exudates into the plant rhizosphere to inhibit the nitrification process, is a hypothesized adaptive mechanism for maximizing N uptake. To date, few studies have investigated the temporal pattern and components of root exudates by Australian native plant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…However, there was a negative correlation between DOC and amoA transcript abundance in our study, which was also observed in estuarine ecosystems ( Happel et al, 2019 ). Many studies have observed that nitrification rates can be inhibited by increased organic C concentration in terrestrial ecosystems due to (1) biological nitrification inhibition ( Elroy & Sunil, 1973 ; Janke, Wendling & Fujinuma, 2018 ; Subbarao et al, 2009 ; White, 1986 ); (2) phenolics, tannins, and monoterpenes promoting heterotrophic immobilization of ammonium and decreasing substrate availability for nitrifiers ( Bremner & McCarty, 1993 ; Paavolainen, Kitunen & Smolander, 1998 ); and (3) the increased competition between heterotrophic and nitrifying bacteria for ammonium caused by high quality C ( i.e., labile carbon) ( Strauss & Lamberti, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a negative correlation between DOC and amoA transcript abundance in our study, which was also observed in estuarine ecosystems ( Happel et al, 2019 ). Many studies have observed that nitrification rates can be inhibited by increased organic C concentration in terrestrial ecosystems due to (1) biological nitrification inhibition ( Elroy & Sunil, 1973 ; Janke, Wendling & Fujinuma, 2018 ; Subbarao et al, 2009 ; White, 1986 ); (2) phenolics, tannins, and monoterpenes promoting heterotrophic immobilization of ammonium and decreasing substrate availability for nitrifiers ( Bremner & McCarty, 1993 ; Paavolainen, Kitunen & Smolander, 1998 ); and (3) the increased competition between heterotrophic and nitrifying bacteria for ammonium caused by high quality C ( i.e., labile carbon) ( Strauss & Lamberti, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expanding body of literature on BNI suggests that many plant species may be capable of reducing nitrification in the rhizosphere (Chowdhury et al, 2017;Coskun et al, 2017a;Janke et al, 2018;Subbarao et al, 2007). In the agricultural setting, direct and indirect suppression of nitrification could reduce NO 3 − losses from annual cropping systems, with the agronomic benefit of increased fertilizer use efficiency and environmental benefits of reduced NO 3 − flow into downstream waterways and N 2 O emissions into the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…A suitable sediment NH 4 -N range for V. natans has been reported as 5-50 mg/kg (Zhu et al, 2006). Although only a few nitri cation inhibition agents from root exudates have been identi ed, BNI activity was con rmed in different plant species, blocking either the ammonia monooxygenase (AMO) pathway or both the AMO and hydroxylamine oxidoreductase (HAO) pathways (Sun et al, 2016, Janke et al, 2018. BNI function is thought to be triggered by the synergistic effect of NH 4 -N presence and low pH in the root environment (Subbarao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%